Smart Q / Muhammad Azlie Md Isa and Norarifah Ali - Md Isa, Muhammad Azlie; Ali, Norarifah (Faculty of Art and Design, 2021)
Pandemic covid-19 is a very dangerous pandemic. We should work together to break this covid-19 chain. Among the things that need to be done is to maintain social distance while in public places. However, we find it difficult to practice social distancing when we are in a crowded place. This is because some people do not care about this pandemic issue. Social distancing is the practice of purposefully reducing close contact between people. It means to maintain a distance of about 1-2 metres from others when possible, avoiding gatherings and remaining out of crowded areas as much as possible. Therefore, this product is produced to help the public comply with S.O.P. The design was based on the issue of Covid-19 and the product design for public users at crowded places. The problem they are facing is people find it difficult to social distancing themselves when in a public place, while social distancing product that is less effective will make some people do not follow the prescribed of social distancing and some people do not know how important social distancing is to breaking the Covid-19 chain. This product is named SmartQ which is smart is “pintar” and Q stands for queue. SmartQ is a barrier with minimalism style for social distancing in public places. This product uses minimalism because it will be placed in a crowded place. So, minimalism style can make the situation calmer and more comfortable.